2020
DOI: 10.3390/toxins12110713
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Berberine—A Summary Update

Abstract: Berberine is a plant metabolite belonging to the group of isoquinoline alkaloids with strong biological and pharmacological activity. Currently, berberine is receiving considerable interest due to its anticancer activity based on many biochemical pathways, especially its proapoptotic and anti-inflammatory activity. Therefore, the growing number of papers on berberine demands summarizing the knowledge and research trends. The efficacy of berberine in breast and colon cancers seems to be the most promising aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 119 publications
(181 reference statements)
1
85
0
Order By: Relevance
“…BBR has a wide range of pharmacological and therapeutic effects, and BBR has been widely used for its antimicrobial and antiprotozoal activities ( 2 ). Recently, as research continues, BBR has also been found to play a role in mood disorders ( 3 ), high blood pressure ( 4 ), hypercholesterolemia ( 5 ), hyperlipidemia ( 5 ), diabetes ( 6 ), heart failure ( 7 ), colorectal cancer ( 8 ), and other diseases. Because of its many effects, BBR is as commonly used as are aspirin and metformin.…”
Section: Introductionmentioning
confidence: 99%
“…BBR has a wide range of pharmacological and therapeutic effects, and BBR has been widely used for its antimicrobial and antiprotozoal activities ( 2 ). Recently, as research continues, BBR has also been found to play a role in mood disorders ( 3 ), high blood pressure ( 4 ), hypercholesterolemia ( 5 ), hyperlipidemia ( 5 ), diabetes ( 6 ), heart failure ( 7 ), colorectal cancer ( 8 ), and other diseases. Because of its many effects, BBR is as commonly used as are aspirin and metformin.…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies have revealed that berberine also possesses anti-diabetic ( Yin et al, 2008 ), hypolipidemic ( Kong et al, 2004 ), anti-inflammatory ( Habtemariam, 2016 ), immunosuppressive ( Li et al, 2016 ) and anti-cancer ( Liu et al, 2019 ) activities. In addition to Asian countries, berberine has currently received great interest in European ( Och et al, 2020 ) and also gained entry in African countries as a dietary supplement ( Alolga et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Berberine, a well-known isoquinoline alkaloid of the protoberberine type, is distributed among the Berberidaceae, Papaveraceae, and Ranunculaceae plant families and mostly isolated from different Berberis species [ 20 , 21 ]. Berberine is known for its proapoptotic and autophagic potential against many types of cancer but also for its chemosensitizing properties suggesting its use in combination therapy [ 21 , 22 , 23 ]. With regard to MM, berberine downregulated miRNA-21 expression and significantly upregulated programmed cell death 4 (PDCD4) leading to apoptosis and G2 phase cell cycle arrest in RPMI8226 cells [ 17 ].…”
Section: Resultsmentioning
confidence: 99%